2014
DOI: 10.1007/s00405-014-3209-x
|View full text |Cite
|
Sign up to set email alerts
|

How head and neck consultants manage patients’ emotional distress during cancer follow-up consultations: a multilevel study

Abstract: Abstract:Objectives: Head and neck cancer (HNC) patients suffer substantial emotional problems. This study aimed to explore how utterance-level variables (source, type and timing of emotional cues) and patient-level variables (e.g. age, gender and emotional wellbeing) relate to consultants' responses (i.e. reducing or providing space) to patient expressions of emotional distress.Methods: Forty-three HNC outpatient follow-up consultations were audio recorded and coded, for patients' expressions of emotional dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 26 publications
4
28
2
Order By: Relevance
“…This finding suggested that GPs were adopting complex strategies in dealing with subtle emotional issues expressed by their patients in consultations, which is consistent with the findings reported in a recent study with head and neck cancer consultants [10]. GPs, similar to oncology consultants, are faced with a patient population with diverse backgrounds and complex disease conditions.…”
Section: Effects Of Multimorbidity and Deprivation On Gp Providing Spsupporting
confidence: 89%
See 2 more Smart Citations
“…This finding suggested that GPs were adopting complex strategies in dealing with subtle emotional issues expressed by their patients in consultations, which is consistent with the findings reported in a recent study with head and neck cancer consultants [10]. GPs, similar to oncology consultants, are faced with a patient population with diverse backgrounds and complex disease conditions.…”
Section: Effects Of Multimorbidity and Deprivation On Gp Providing Spsupporting
confidence: 89%
“…Compared with studies using the same VR-CoDES measure in the oncology setting (mean = 3 -4 per interview [8,10,23] the mean frequency of cue/concern expression per consultation was higher (mean = 13.68) in our sample from the primary care setting. This might be partly explained by the proportion (approximately 50%) of participants with multimorbidity, a complex condition often associated with depression and psychological discomfort [24,25], which increases emotionally loaded expressions.…”
Section: Multimorbidity and Patient's Expression Of Emotional Distresscontrasting
confidence: 83%
See 1 more Smart Citation
“…When and the way in which concerns are presented during the consultation can also impact whether they are met by empathy and given space, or shut down [2][3][4]. Furthermore, Kennifer et al [5] found that the intensity and type of emotional concern (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…We were motivated to conduct our research with clinical interactions, in the oncology field, that are frequently interspersed with emotional content, as has been previously shown by our group [3] and others [2]. Patients, in cancer clinics especially, may hide their emotions through embarrassment, a wish not to burden others, accepting anxiety as part of treatment or because they were not asked about additional concerns [12].…”
Section: Introductionmentioning
confidence: 99%